Estimation of cardiac reserve by peak power: validation and initial application of a simplified index - Armstrong, G P; Carlier, S G; Fukamachi, K; Thomas, J D; Marwick, T H (Heart (British Cardiac Society), 1999)
OBJECTIVES To validate a simplified estimate of peak power (SPP) against true (invasively measured) peak instantaneous power (TPP), to assess the feasibility of measuring SPP during exercise and to correlate this with functional capacity. DESIGN Development of a simplified method of measurement and observational study. SETTING Tertiary referral centre for cardiothoracic disease. SUBJECTS For validation of SPP with TPP, seven normal dogs and four dogs with dilated cardiomyopathy were studied. To assess feasibility and clinical significance in humans, 40 subjects were studied (26 patients; 14 normal controls). METHODS In the animal validation study, TPP was derived from ascending aortic pressure and flow probe, and from Doppler measurements of flow. SPP, calculated using the different flow measures, was compared with peak instantaneous power under different loading conditions. For the assessment in humans, SPP was measured at rest and during maximum exercise. Peak aortic flow was measured with transthoracic continuous wave Doppler, and systolic and diastolic blood pressures were derived from brachial sphygmomanometry. The difference between exercise and rest simplified peak power (Δ SPP) was compared with maximum oxygen uptake (V˙O2max), measured from expired gas analysis. RESULTS SPP estimates using peak flow measures correlated well with true peak instantaneous power (r = 0.89 to 0.97), despite marked changes in systemic pressure and flow induced by manipulation of loading conditions. In the human study, V˙O2max correlated with Δ SPP (r = 0.78) better than Δ ejection fraction (r = 0.18) and Δ rate–pressure product (r = 0.59). CONCLUSIONS The simple product of mean arterial pressure and peak aortic flow (simplified peak power, SPP) correlates with peak instantaneous power over a range of loading conditions in dogs. In humans, it can be estimated during exercise echocardiography, and correlates with maximum oxygen uptake better than ejection fraction or rate–pressure product.